Early christianity and 'the homosexual' : a postscript to a blasphemy trial and challenge to Mrs. Whitehouse (in 'measured tones). - Smith, Don (London : Quantum Jump, 1977)
Fonds Suzan Daniel (FSD)
Engels
Brochure